Roberts, Europe 1880-1945 - van Hartesveldt, Fred (Teaching History: A Journal of Methods, 1991)
J.M. Roberts has written a traditional history, the sort of history for which Jacques Barzun pleads with wit and eloquence in Clio and the Doctors (Chicago, 1974). Europe 1880-1945 is a narrative built on a chronological frame with the author's comments and analysis included as digressions. As Barzun says the historian should, Roberts has eschewed graphs and tables and charts, preferring to use words to explain even economic trends. Though the methodology might be thought, by some, old fashioned, the book is filled with not only facts but also astute comments about what those facts meant for the development of European society. Although it is unlikely that author and publisher predicted the recent revolutionary events in Eastern Europe, their timing for the issuing of this book could hardly have been better. Confusion about these changes is widespread, and Roberts-who seems to have a taste for diplomatic history--provides a good foundation for understanding not only the regional problems with the Soviet system but also the ethnic problems that have produced violence in a number of places. He is able to give due attention to the Great Powers before, during, and between the World Wars without allowing the Lithuanias and Bulgarias (or for that matter, the Sanjak of Novi Bazar) to get lost. This volume is certainly appropriate for anyone who wants to understand the current situation in Europe.